PENGARUH PEMBERIAN BERBAGAI KONSENTRASI ETHEPON TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN VARIETAS LOKAL DAN ANTARA (Cucumis sativus L.) - Novita Hera; Zulfadly Syarif; Irawati Chaniago (Jurnal Agroteknologi, 2018)
Research on the effect of giving various concentration ethepon to growth and production of cucumber was conducted in Nagari Kacang Kecamatan X Koto Singkarak, Solok, West Sumatra, from June to August 2008. The objectives of the study were (1) get interaction between several concentrations of ethephon with cucumber varieties, (2) obtaining the best ethepon concentration, (3) and knowing cucumber varieties that have better production. Factorial-factored experiments in Randomized Block Design with 2 factors and 3 groups. The first factor of ethepon concentration consisted of five levels 0, 100, 200, 300, 400 ppm. The second factor is cucumber varieties of Local and  Antara varieties. Observed variables: plant length, number of branches, when first male flowers appear, when the first female flowers appear, the number of male flowers, the number of female flowers, the number of straight fruit, the number of fruit is not straight, the fruit weight is straight, fruit weight is not straight. Providing ethepon concentration with crop varieties has an effect on growth and production of cucumber , that is when the first male flowers appear (hst). Provision of ethepon concentration of 200 ppm showed a better effect on the number of female flowers, the number of straight fruit, and the weight of the fruit straight. Factor varieties, singularly different to plant length variables, when the first female flowers appear, the number of straight fruit, the number of crooked fruit, the weight of the fruit straight, and the weight of the bent fruit. Local varieties show better production than Antara varieties.